How the past becomes the past: The temporal positioning of collective memory. (5th August 2021) - Adams, Tracy; Edy, Jill A.
Abstract: Recognizing that the past does not necessarily pass of its own accord but rather is made to pass is crucial for understanding relationships between collective memory, temporality and the past. Analyzing processes of temporal negotiation reveals that changing the ending (or, in some cases creating one at all) requires re‐envisioning the entire sequence of events. Thus, the ending (if there is one) depends on the beginning. British prime ministers' references to 9/11 in public addresses demonstrate this process of temporal negotiation about whether and how to create an ending. Tony Blair constructed the attacks as a legacy, thus sustaining the past as part of the present. To unwind this construction and consign 9/11 to the past, Gordon Brown and David Cameron needed to disrupt the flow of contingent incidents in which Blair had embedded 9/11. By redefining the narrative's beginning, they made it possible to bring 9/11 to an end.